A controllable degradation medical orthopedic magnesium-ceramic glass composite stent and a preparation method thereof

By mixing magnesium alloy with bioceramic glass powder and performing surface treatment, a controllable degradation magnesium-bioceramic glass composite scaffold was prepared, which solved the problem of excessively rapid corrosion rate of magnesium alloy implants, achieved controllable degradation and excellent mechanical properties, and met the needs of medical orthopedic implant materials.

CN122097699APending Publication Date: 2026-05-29SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411731604.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2026-05-29

AI Technical Summary

Technical Problem

Magnesium alloy implants corrode too quickly in the body, causing the mechanical support to fail, resulting in air bubbles and cavitation cavities, which affect the bone healing process, exacerbate inflammation, and lead to volume occupancy issues due to the inability of traditional inert materials to degrade.

Method used

A scaffold structure was prepared by mixing magnesium alloy with bioceramic glass powder and using LPBF technology. The surface was then treated with micro-arc oxidation and polymer coating to regulate the degradation rate and mechanical properties.

Benefits of technology

The controlled degradation of magnesium-bioceramic glass composite scaffolds was achieved, improving mechanical support and osteoconductivity. The degradation rate was 0.4-0.7 mm/y, and the mechanical properties were significantly improved, meeting the needs of medical orthopedic implant materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122097699A_ABST
    Figure CN122097699A_ABST
Patent Text Reader

Abstract

The application provides a controllable degradation medical orthopedic magnesium-ceramic glass composite stent and a preparation method thereof. The preparation method comprises the following steps: mixing a magnesium alloy powder and a ceramic glass powder; printing a composite material stent by using a laser powder bed melting technology; and performing surface treatment on the composite material stent, and then performing high polymer coating surface treatment, so that the controllable degradation medical orthopedic magnesium-ceramic glass composite stent is obtained; wherein the magnesium alloy is a Mg-Y-Gd-Zr magnesium alloy; and the ceramic glass is selected from hydroxyapatite, beta-tricalcium phosphate, bioglass, ZrO2 and the like. The stent structure suitable for bone defect model construction is prepared by using the laser powder bed melting technology, the surface treatment technology is used for realizing the regulation and control of the mechanics and biological activity of the stent, the magnesium-ceramic glass composite stent with good hydrophilicity, controllable degradation, high strength and good bone conduction is successfully prepared, and the urgent needs of the stent material for long-term mechanical support, controllable degradation and good osteogenic induction effect of the medical orthopedic implant material can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of additive manufacturing and surface treatment technology of magnesium-ceramic glass composite materials, specifically to a controllable degradable magnesium-ceramic glass composite orthopedic scaffold and its preparation method, and more particularly to a method for preparing a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold by combining magnesium alloy and bioceramic glass materials, using laser powder bed fusion (LPBF) technology and subsequent micro-arc oxidation (MAO) and polymer surface treatment technology. Background Technology

[0002] Magnesium alloys possess a Young's modulus close to that of natural bone, theoretically minimizing bone atrophy due to stress shielding. Complete biodegradability is a major benefit of magnesium alloy bioimplants, eliminating the need for subsequent surgical removal after bone healing. In this context, magnesium-based alloys can be classified as representative of third-generation biomaterials, possessing a synergistic ability to enhance biodegradability, biocompatibility, and tissue remodeling. However, magnesium alloy implants tend to exhibit high corrosion rates in simulated body fluid (SBF) or corrosive media. Hydrogen release during degradation can generate bubbles that cause separation of surrounding tissue from the implant, negatively impacting the healing process. Cavitation can exacerbate inflammation and nonunion. Furthermore, the rapid initial corrosion of magnesium alloys prevents them from providing mechanical support, limiting their application as medical orthopedic implant materials.

[0003] Bioceramic glass materials can chemically bond with bone tissue, promoting the integration of bone tissue and the material. Some bioactive glass materials also possess antibacterial properties. By combining them with different bioceramic glasses, the degradation rate of magnesium alloy materials can be effectively regulated, resulting in a more gradual degradation process. This ensures that the degradation of the material matches the tissue repair process, thereby better matching the bone healing process.

[0004] The development of surface treatment technology has provided new design ideas and manufacturing processes for the corrosion protection and preparation of magnesium alloy materials. Micro-arc oxidation, also known as plasma electrolysis or micro-arc plasma oxidation, is a surface treatment technology that uses plasma assistance to grow ceramic films in situ on the alloy surface based on anodic oxidation. The oxide film grows in situ, reacts chemically with the alloy substrate, and exhibits good adhesion, hardness, wear resistance, and improved corrosion resistance. The oxide film coating also enhances the biocompatibility of the material and is easily combined with other coatings to create composite coatings. Biodegradable polymers, with mechanical properties closer to those required for implantable materials, are non-toxic, do not affect normal cell proliferation, and have already received FDA approval for implantation as biofunctional materials in clinical and scientific research applications.

[0005] Ideal bone tissue engineering scaffolds require a three-dimensionally interconnected porous structure to facilitate bone tissue growth and nutrient transport. Simultaneously, the introduction of this porous structure can reduce the elastic modulus of medical-grade metallic materials, preventing stress shielding effects. In modern manufacturing technology, additive manufacturing (AM) is a rapid prototyping technology based on layer-by-layer processes to form 3D structures. Due to its precise control over complex structural shapes, additive manufacturing technology exhibits unique advantages in the fabrication of bone tissue engineering scaffolds. Currently, additively manufactured metal-based porous scaffolds are widely researched and clinically applied. The porous structure of the scaffold facilitates cell attachment, diffusion, and growth, thereby promoting tissue regeneration, such as in bone. LPBF additive manufacturing can form more complex topological porous scaffolds with a wider range of porosity control. This is mainly due to the unique layer-by-layer fabrication method of LPBF technology, which allows for more precise control of pore characteristics. Furthermore, the high cooling rate of the LPBF process can refine the microstructure, resulting in relatively higher mechanical strength for LPBF-manufactured magnesium alloy scaffolds.

[0006] Furthermore, LPBF technology offers flexibility in material design, allowing researchers to optimize the microstructure and structure of magnesium alloy scaffolds by adjusting laser parameters and scanning strategies to tailor material properties to specific application requirements. Therefore, LPBF not only improves the fabrication efficiency of magnesium alloy scaffolds but also opens up new avenues for enhancing their application potential.

[0007] By comprehensively utilizing these technological advantages, this invention aims to develop a magnesium-bioceramic glass composite medical orthopedic implant scaffold with good hydrophilicity, controllable degradation, high strength, and good osteoconductivity, which can meet the urgent need for magnesium alloy scaffolds in medical orthopedic implants for long-term mechanical support, controllable degradation, and good osteogenic induction effect. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. This invention utilizes the lightweight properties of magnesium alloys, mixing them with glass-ceramic powder, and employing LPBF to prepare a scaffold structure conducive to bone tissue growth. Furthermore, the scaffold undergoes surface treatment, thereby solving problems such as the rapid corrosion rate of traditional magnesium alloy implants leading to premature failure of mechanical support, air bubble formation negatively impacting the healing process, cavitation causing exacerbated inflammation, and nonunion. Simultaneously, the unique porous structure ensures coordination between material degradation and bone tissue healing, avoiding the volume occupation effect caused by the non-degradability of traditional inert materials. This invention meets the urgent need for orthopedic implant materials with long-term mechanical support, controllable degradation, and good osteogenic induction effects.

[0009] The magnesium-bioceramic glass composite scaffold prepared by the method of this invention not only has excellent comprehensive mechanical properties, but also has a controllable degradation rate, which can meet the urgent need of medical orthopedic implant materials for implant scaffolds with long-term mechanical support and controllable degradation.

[0010] The objective of this invention is achieved through the following technical solution:

[0011] This invention provides a method for preparing a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold, the method comprising the following steps:

[0012] A. Prepare magnesium alloy powder according to the preset composition;

[0013] B. Mix magnesium alloy powder with ceramic glass powder;

[0014] C. Composite material scaffolds were printed using laser powder bed melting technology;

[0015] D. Perform an oxidation surface treatment on the composite material scaffold;

[0016] E. Perform polymer coating surface treatment on the oxidized surface-treated support;

[0017] In step A, the magnesium alloy is a Mg-Y-Gd-Zr series magnesium alloy.

[0018] In step B, the ceramic glass includes at least one of hydroxyapatite, β-tricalcium phosphate, bioglass, and ZrO2;

[0019] In step C, the parameters for printing using laser powder bed fusion technology include: laser power of 600-800w; layer thickness of 0.02-0.04mm; scanning speed of 400-600mm / s; and interlayer rotation angle of 0-90°.

[0020] As a preferred embodiment, in step A, the magnesium alloy powder is prepared by at least one of the following methods: gas atomization, centrifugal atomization, mechanical pulverization, or plasma rotating electrode method.

[0021] As a preferred embodiment, the magnesium alloy powder has a particle size of 200-300 mesh.

[0022] As a preferred embodiment, in step B, the particle size of the ceramic glass powder is 200-300 nm.

[0023] As a preferred embodiment, the bioglass includes at least one of 13-93 bioglass, 45S5 bioglass, and S53P4 bioglass.

[0024] As a preferred embodiment, the ceramic glass powder has a mass content of 5-30% in the magnesium-ceramic composite powder.

[0025] As a limited option, the magnesium alloy powder and ceramic glass powder are mixed using a ball milling method or a dry particle composite method.

[0026] As a preferred embodiment, in step C, before the laser powder bed melting technology is used for printing, the substrate needs to be heated to 25-400°C; during the printing process, inert gas needs to be introduced to keep the oxygen content in the working chamber below 200ppm.

[0027] As a preferred embodiment, in step D, the oxidation surface treatment is selected from at least one of micro-arc oxidation surface treatment and anodic oxidation surface treatment.

[0028] The preferred conditions for the micro-arc oxidation surface treatment are: a working voltage of 200-400V, an oxidation time of 5-15min, and a duty cycle of 8-12%.

[0029] As a preferred embodiment, the conditions for the anodic oxidation surface treatment are: a working voltage of 100-200V, an oxidation time of 5-15min, and a duty cycle of 8-12%.

[0030] As a preferred embodiment, the electrolyte used in the oxidation surface treatment is mainly a silicate system, and the concentration of the electrolyte is 12-18 g / L.

[0031] As a preferred embodiment, in step D, before the composite material support undergoes oxidation surface treatment, the composite material support is further subjected to electrolytic polishing and acid-base treatment.

[0032] As a preferred embodiment, the electrolyte used in the electropolishing is a mixed solution of nitric acid and alcohol, the voltage is 20-30V, and the polishing time is 2-4 minutes;

[0033] The specific steps of the acid-base treatment are as follows: place the sample in a 6-10 g / L NaHCO3 solution for 8-12 seconds for alkaline washing, then rinse with water, and then wash with an 8-12 g / L phosphoric acid solution for 12-18 seconds, followed by rinsing with water.

[0034] As a preferred embodiment, in step E, the specific operation of performing the polymer coating surface treatment is as follows: the composite material scaffold is immersed in an extraction solution containing polymer materials for immersion treatment; the immersion time is 3-6s, and the immersion speed is 1-3cm / s.

[0035] As a preferred embodiment, the polymer material is at least one of polylactic acid, polylactic acid-glycolic acid copolymer, polyetheretherketone, and sodium alginate; the molecular weight of the polymer material is 400,000-600,000 Daltons.

[0036] As a preferred embodiment, the mass concentration of the polymer material in the extraction solution is 8-12%.

[0037] As a preferred embodiment, step E further includes a step of treating the composite material scaffold with silane before performing the polymer coating surface treatment.

[0038] As a preferred embodiment, the specific operation of the silane treatment is as follows: immerse the composite material scaffold in a silane coupling agent solution for 2-4 minutes, then lift it twice at a lifting speed of 0.7-1.2 cm / s, and then dry it.

[0039] As a preferred embodiment, in the preparation method, magnesium alloy powder with a particle size of 200-300 mesh and ceramic glass powder with a particle size of 240-300 mesh are used; the ceramic glass is selected from S53P4 bioglass, hydroxyapatite, and 13-93 bioglass, with a content of 5-30%; the printing parameters are: laser power of 600-800w, scanning speed of 400-600mm / s, layer thickness of 0.02-0.04mm, and interlayer rotation angle of 30-90°; the oxidation voltage used for micro-arc oxidation surface treatment is 250-40... The extraction process was carried out at 0V for 5-15 minutes. The polymer materials used for the polymer extraction treatment were polyetheretherketone, polylactic acid, and sodium alginate, with a molecular weight of 500,000-600,000 Daltons. The extraction time was 3-4 seconds, and the extraction speed was 2-3 cm / s. The magnesium-ceramic glass composite scaffolds prepared in this way (Examples 4 / 8 / 11 / 14 below) had a room temperature compressive strength (UCS) of 111-140 MPa, a Young's modulus (E) of 59-65 GPa, and a corrosion rate of 0.45-0.56 mm / y.

[0040] This invention provides a controllable degradable orthopedic magnesium-ceramic glass composite scaffold prepared according to the aforementioned method. By mixing magnesium alloy powder and bioceramic glass, this invention effectively regulates the degradation rate of the magnesium alloy material, making its degradation more stable. Furthermore, surface treatment of the printed magnesium-bioceramic glass composite scaffold using a polymer / oxide film composite coating technique further delays the degradation rate of the magnesium alloy scaffold. In vivo, the bioceramic glass can induce the formation of an apatite layer, forming a chemical bond with bone tissue and promoting bone regeneration. The apatite layer formed by the bioglass material in body fluids is beneficial for osteoblast adhesion and proliferation, and the degradation products of magnesium (magnesium ions) can also promote osteoblast activity, exhibiting significant osteoinductive ability. The osteoconductive effect of the magnesium-bioceramic glass composite scaffold is effectively improved, and the mechanical support effect and the synchronous coordination effect between the magnesium-bioceramic glass composite scaffold and bone regeneration are also enhanced.

[0041] Compared with the prior art, the present invention has the following advantages:

[0042] 1. Excellent Mechanical Properties: This invention prepares magnesium-bioceramic glass composite scaffold materials via LPBF and performs surface treatment on the scaffolds, significantly improving their mechanical properties. The magnesium-bioceramic glass composite scaffold materials prepared by this method have a room temperature compressive yield strength (UCS) of 90-140 MPa and a Young's modulus (E) of 53-65 GPa.

[0043] 2. Excellent corrosion resistance: By controlling the printing process and performing surface treatment on the magnesium-bioceramic glass composite scaffold, this invention significantly improves the corrosion resistance of the magnesium-bioceramic glass composite scaffold. The degradation rate of the magnesium-bioceramic glass composite scaffold prepared by the method of this invention in simulated human body fluid is controlled at 0.4-0.7 mm / y.

[0044] 3. Controllable Fabrication Process: LPBF technology offers flexibility and controllability in new material design. By adjusting printing process parameters such as laser parameters and scanning strategies, and designing different surface treatment regimes, the physicochemical and biological properties of magnesium alloy scaffolds can be effectively controlled. This provides new ideas and processes for the development of novel controllable degradable osteoconductive magnesium-bioceramic glass composite scaffolds, improving the fabrication efficiency of magnesium-bioceramic glass composite scaffolds, shortening the research and development cycle, and reducing research costs.

[0045] 4. Broad application prospects: The biodegradable, long-term mechanically supportive, osteogenic magnesium-bioceramic glass composite scaffold in this invention can meet the urgent need for medical orthopedic implant materials for scaffold materials with controllable degradation and excellent osteoconductive effect. Attached Figure Description

[0046] Other features, objects, and advantages of the invention will become more apparent from the following detailed description of non-limiting examples with reference to the accompanying drawings:

[0047] Figure 1 A schematic diagram of the fabrication process of a controllable degradable magnesium-bioceramic glass composite scaffold;

[0048] Figure 2 This is a morphological image of the controllable degradable WE43 magnesium-bioceramic glass composite scaffold obtained by LPBF additive manufacturing polymer / MAO surface treatment according to Example 14 of the present invention; wherein Figure 2 (a) SEM morphology of the magnesium-bioceramic glass composite scaffold after MAO treatment. Figure 2 (b) shows the stereomicroscopic morphology of the magnesium-bioceramic glass composite scaffold after MAO treatment. Detailed Implementation

[0049] The present invention will be described in detail below with reference to specific examples. These examples will help those skilled in the art to further understand the invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0050] The raw materials used in the following embodiments are all obtained through conventional means, and the present invention does not impose any special limitations.

[0051] The specific methods used in the following embodiments for preparing alloy powders are gas atomization, centrifugal atomization, mechanical pulverization, or plasma rotating electrode method. These are all conventional powder preparation methods, and it is only necessary to obtain powders of the corresponding particle size. This invention does not impose any special limitations.

[0052] The specific powder mixing methods in the following embodiments are ball milling or dry particle composite methods, which are all conventional powder mixing methods. As long as the powder is mixed, the present invention does not impose any special limitations on the specific preparation process conditions.

[0053] The mechanical property tests conducted in the following examples are performed using the methods specified in GB / T 7314-2017 "Metallic Materials - Room Temperature Compression Test Method".

[0054] The in vitro degradation experiments conducted in the following examples were performed using the methods described in ISO 10993-15:2000, "Biological evaluation of medical devices—Part 15: Qualitative and quantitative analysis of degradation products of metals and alloys".

[0055] Example 1

[0056] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method (e.g. Figure 1 (As shown). The specific steps of the preparation method are as follows:

[0057] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional gas atomization method, with a particle size of 250 mesh.

[0058] 2) The magnesium alloy powder screened in step 1) is mixed with 200nm hydroxyapatite ceramic powder, and the mass percentage of hydroxyapatite powder in the mixed powder is 10%. Ball milling is used for the mixing process, and the specific steps are as follows:

[0059] 2.1 Mix the magnesium alloy powder and hydroxyapatite ceramic powder evenly. Place the mixed powder in ethanol and ultrasonically disperse for 10 minutes to ensure uniform mixing.

[0060] 2.2 Pour the ultrasonically dispersed powder into a zirconia ball mill jar. Add an appropriate amount of ethanol as a dispersion medium. Add zirconia balls, setting the ball-to-powder ratio (weight ratio of ball milling medium to powder) to 10:1.

[0061] 2.3 Sealed grinding jar, installed on a planetary ball mill. Set the ball mill parameters: rotation speed 500 rpm, grinding time 12 hours, grinding mode alternating forward and reverse (changing direction every 2 hours).

[0062] 2.4 After ball milling, remove the milling jar and open the lid. Pour out the mixture of milled powder and ethanol, and separate the powder by filtration or centrifugation. Wash the powder with ethanol to remove residual milling media and unreacted substances. Place the washed powder in a vacuum drying oven and dry at 80°C for 14 hours to ensure complete drying.

[0063] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 600W, the scanning speed to 400mm / s, the layer thickness to 0.02mm, and the interlayer rotation angle to 0°. Before printing, the substrate is heated to 400℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0064] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment. The electrolyte used for electrolytic polishing is a mixed solution of nitric acid and alcohol. The voltage used is 20-30V and the polishing time is 2-4 minutes.

[0065] After polishing, the sample was subjected to acid and alkali treatment. It was placed in an 8 g / L NaHCO3 solution for alkali washing for 10 seconds, then rinsed once with distilled water. After rinsing, it was acid washed with a 10 g / L phosphoric acid solution for 15 seconds, and then rinsed a second time with distilled water.

[0066] The micro-arc oxidation electrolyte used consisted of 15 g / L Na2SiO4, 5 g / L NaOH, and 1 g / L EDTA-2Na. The oxidation voltage was 350 V, the time was 10 min, and the duty cycle was 10%.

[0067] 5) Perform polymer extraction treatment on the samples after micro-arc oxidation surface treatment. Before polymer extraction, perform silane coupling treatment. Immerse the composite material scaffold in silane coupling agent (KH550) solution for 2-4 minutes, then lift it twice at a lifting speed of 1cm / s, and then dry it.

[0068] The polymer extraction solution used was a 10% polymer material concentration solution. The selected polymer material was polylactic acid with a molecular weight of 600,000 Daltons. The extraction time was 3 seconds and the extraction speed was 3 cm / s.

[0069] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0070] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 58 MPa, Young's modulus (E): 48 GPa, corrosion rate: 1.2 mm / y.

[0071] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 98 MPa, Young's modulus (E): 64 GPa, corrosion rate: 0.5 mm / y.

[0072] Example 2

[0073] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0074] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional centrifugal atomization method, with a particle size of 200 mesh.

[0075] 2) The magnesium alloy powder screened in step 1) is mixed with 250nm 13-93 bioglass powder, and the mass percentage of 13-93 bioglass powder in the mixed powder is 5%. A dry particle mixing method is used, and the specific steps are as follows:

[0076] 2.1 Place magnesium alloy powder and 13-93 bioglass powder in a dry particle mixing device, and introduce argon gas for gas exchange to reduce the oxygen content in the device.

[0077] 2.2 Start the dry mixing equipment at a speed of 1200 r / s for 20 min. Remove the mixed powder and dry it.

[0078] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 700W, the scanning speed to 500mm / s, the layer thickness to 0.03mm, and the interlayer rotation angle to 30°. Before printing, the substrate is heated to 200℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0079] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0080] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 250V, the time is 5min, and the duty cycle is 10%.

[0081] 5) Perform polymer extraction on the sample after micro-arc oxidation surface treatment. Before polymer extraction, perform silane coupling treatment (the specific steps are the same as step 5 in Example 1). The polymer extraction solution used is a solution with a polymer material mass concentration of 10%. The polymer material is selected as polylactic acid-glycolic acid copolymer with a molecular weight of 400,000 Daltons. The extraction time is 5s and the extraction speed is 2cm / s.

[0082] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0083] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 56 MPa, Young's modulus (E): 71 GPa, corrosion rate: 1.5 mm / y.

[0084] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 90 MPa, Young's modulus (E): 62 GPa, corrosion rate: 0.65 mm / y.

[0085] Example 3

[0086] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0087] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional mechanical pulverization method, with a particle size of 300 mesh.

[0088] 2) The magnesium alloy powder screened in step 1) is mixed with 200nm 45S5 bioglass powder, and the mass percentage of 45S5 bioglass powder in the mixed powder is 20%. Dry particle mixing is used (the specific steps are the same as step 2 in Example 2).

[0089] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 800W, the scanning speed to 600mm / s, the layer thickness to 0.02mm, and the interlayer rotation angle to 90°. Before printing, the substrate is heated to 400℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0090] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0091] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 400V, the time is 15min, and the duty cycle is 10%.

[0092] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as the silane coupling treatment in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was sodium alginate with a molecular weight of 500,000 Daltons. The extraction time was 6s and the extraction speed was 1cm / s.

[0093] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0094] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 56 MPa, Young's modulus (E): 74 GPa, corrosion rate: 1.35 mm / y.

[0095] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 90 MPa, Young's modulus (E): 60 GPa, corrosion rate: 0.62 mm / y.

[0096] Example 4

[0097] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0098] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional ion rotating electrode method, with a particle size of 250 mesh.

[0099] 2) The magnesium alloy powder screened in step 1) is mixed with 300nm S53P4 bioglass powder, and the mass percentage of S53P4 bioglass powder in the mixed powder is 30%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0100] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 650W, the scanning speed to 450mm / s, the layer thickness to 0.04mm, and the interlayer rotation angle to 60°. Before printing, the substrate is heated to 250℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0101] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0102] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 300V, the time is 10min, and the duty cycle is 10%.

[0103] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as the silane coupling treatment in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polyether ether ketone with a molecular weight of 600,000 Daltons. The extraction time was 3s and the extraction speed was 2cm / s.

[0104] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0105] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 64 MPa, Young's modulus (E): 80 GPa, corrosion rate: 1.08 mm / y.

[0106] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 140 MPa, Young's modulus (E): 62 GPa, corrosion rate: 0.45 mm / y.

[0107] Example 5

[0108] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0109] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional ion rotating electrode method, with a particle size of 200 mesh.

[0110] 2) Mix the magnesium alloy powder screened in step 1) with 250nm β-tricalcium phosphate powder. The mass percentage of β-tricalcium phosphate powder in the mixed powder is 15%. The mixing process is carried out by dry particle method (the specific steps are the same as step 2 in Example 2).

[0111] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 600W, the scanning speed to 550mm / s, the layer thickness to 0.02mm, and the interlayer rotation angle to 30°. Before printing, the substrate is heated to 150℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0112] 4) The obtained printed parts are subjected to anodizing surface treatment. Before oxidation, electropolishing and acid-base treatment are performed (the specific steps are the same as step 4 in Example 1).

[0113] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 100V, the time is 5min, and the duty cycle is 10%.

[0114] 5) The sample after anodizing surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as those in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polylactic acid-glycolic acid copolymer with a molecular weight of 450,000 Daltons. The extraction time was 4s and the extraction speed was 5cm / s.

[0115] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0116] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 57 MPa, Young's modulus (E): 66 GPa, corrosion rate: 1.38 mm / y.

[0117] After polymer / anodic oxidation surface treatment: room temperature compressive strength (UCS): 94 MPa, Young's modulus (E): 57 GPa, corrosion rate: 0.63 mm / y.

[0118] Example 6

[0119] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0120] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional gas atomization method, with a particle size of 200 mesh.

[0121] 2) The magnesium alloy powder screened in step 1) is mixed with 300nm ZrO2 bioglass powder, and the mass percentage of ZrO2 bioglass powder in the mixed powder is 20%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0122] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 750W, the scanning speed to 400mm / s, the layer thickness to 0.04mm, and the interlayer rotation angle to 45°. Before printing, the substrate is heated to 350℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0123] 4) The obtained printed parts are subjected to anodizing surface treatment. Before oxidation, electropolishing and acid-base treatment are performed (the specific steps are the same as step 4 in Example 1).

[0124] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 150V, the time is 8min, and the duty cycle is 10%.

[0125] 5) The sample after anodizing surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as those in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polylactic acid with a molecular weight of 550,000 Daltons. The extraction time was 3s and the extraction speed was 1cm / s.

[0126] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0127] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 74 MPa, Young's modulus (E): 68 GPa, corrosion rate: 1.33 mm / y.

[0128] After polymer / anodic oxidation surface treatment: room temperature compressive strength (UCS): 104 MPa, Young's modulus (E): 58 GPa, corrosion rate: 0.64 mm / y.

[0129] Example 7

[0130] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0131] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional centrifugal atomization method, with a particle size of 220 mesh.

[0132] 2) Mix the magnesium alloy powder screened in step 1) with 280nm 45S5 ceramic glass powder. The mass percentage of 45S5 ceramic glass powder in the mixed powder is 10%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 2).

[0133] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 600W, the scanning speed to 400mm / s, the layer thickness to 0.03mm, and the interlayer rotation angle to 60°. Before printing, the substrate is heated to 200℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0134] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0135] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 300V, the time is 10min, and the duty cycle is 10%.

[0136] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as the silane coupling treatment in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polylactic acid with a molecular weight of 500,000 Daltons. The extraction time was 5s and the extraction speed was 2cm / s.

[0137] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0138] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 68 MPa, Young's modulus (E): 63 GPa, corrosion rate: 1.06 mm / y.

[0139] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 95 MPa, Young's modulus (E): 57 GPa, corrosion rate: 0.62 mm / y.

[0140] Example 8

[0141] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0142] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional mechanical pulverization method, with a particle size of 260 mesh.

[0143] 2) Mix the magnesium alloy powder screened in step 1) with 240nm hydroxyapatite powder, and the mass percentage of hydroxyapatite powder in the mixed powder is 20%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0144] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 800W, the scanning speed to 500mm / s, the layer thickness to 0.03mm, and the interlayer rotation angle to 30°. Before printing, the substrate is heated to 250℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0145] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0146] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 250V, the time is 15min, and the duty cycle is 10%.

[0147] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as the silane coupling treatment in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polyether ether ketone with a molecular weight of 500,000 Daltons. The extraction time was 3s and the extraction speed was 2cm / s.

[0148] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0149] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 83 MPa, Young's modulus (E): 73 GPa, corrosion rate: 0.97 mm / y.

[0150] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 116 MPa, Young's modulus (E): 65 GPa, corrosion rate: 0.52 mm / y.

[0151] Example 9

[0152] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0153] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional plasma rotating electrode method, with a particle size of 280 mesh.

[0154] 2) The magnesium alloy powder screened in step 1) is mixed with 220nm β-tricalcium phosphate powder, and the mass percentage of β-tricalcium phosphate powder in the mixed powder is 5%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0155] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 700W, the scanning speed to 500mm / s, the layer thickness to 0.04mm, and the interlayer rotation angle to 0°. Before printing, the substrate is heated to 100℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0156] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0157] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 400V, the time is 10min, and the duty cycle is 10%.

[0158] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as the silane coupling treatment in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was sodium alginate with a molecular weight of 600,000 Daltons. The extraction time was 4s and the extraction speed was 1cm / s.

[0159] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0160] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 62 MPa, Young's modulus (E): 55 GPa, corrosion rate: 0.91 mm / y.

[0161] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 92 MPa, Young's modulus (E): 53 GPa, corrosion rate: 0.56 mm / y.

[0162] Example 10

[0163] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0164] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional plasma rotating electrode method, with a particle size of 260 mesh.

[0165] 2) The magnesium alloy powder screened in step 1) is mixed with 260nm S53P4 bioglass powder, and the mass percentage of S53P4 bioglass powder in the mixed powder is 10%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0166] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 750W, the scanning speed to 550mm / s, the layer thickness to 0.02mm, and the interlayer rotation angle to 45°. Before printing, the substrate is heated to 350℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0167] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0168] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 200V, the time is 5min, and the duty cycle is 10%.

[0169] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as those in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polylactic acid-glycolic acid copolymer with a molecular weight of 400,000 Daltons. The extraction time was 5s and the extraction speed was 2cm / s.

[0170] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0171] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 85 MPa, Young's modulus (E): 66 GPa, corrosion rate: 1.17 mm / y.

[0172] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 93 MPa, Young's modulus (E): 59 GPa, corrosion rate: 0.69 mm / y.

[0173] Example 11

[0174] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0175] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional centrifugal atomization method, with a particle size of 200 mesh.

[0176] 2) The magnesium alloy powder screened in step 1) is mixed with 300nm 13-93 bioglass powder, and the mass percentage of 13-93 bioglass powder in the mixed powder is 30%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0177] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 600W, the scanning speed to 400mm / s, the layer thickness to 0.02mm, and the interlayer rotation angle to 90°. Before printing, the substrate is heated to 100℃, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0178] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0179] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 400V, the time is 10min, and the duty cycle is 10%.

[0180] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as the silane coupling treatment in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polylactic acid with a molecular weight of 600,000 Daltons. The extraction time was 4s and the extraction speed was 3cm / s.

[0181] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0182] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 74 MPa, Young's modulus (E): 75 GPa, corrosion rate: 0.92 mm / y.

[0183] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 128 MPa, Young's modulus (E): 65 GPa, corrosion rate: 0.51 mm / y.

[0184] Example 12

[0185] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0186] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional mechanical pulverization method, with a particle size of 220 mesh.

[0187] 2) The magnesium alloy powder screened in step 1) is mixed with 240nm ZrO2 bioglass powder, and the mass percentage of ZrO2 bioglass powder in the mixed powder is 10%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0188] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 600W, the scanning speed to 500mm / s, the layer thickness to 0.03mm, and the interlayer rotation angle to 0°. Before printing, the substrate is heated to 50°C, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0189] 4) The obtained printed parts are subjected to anodizing surface treatment. Before oxidation, electropolishing and acid-base treatment are performed (the specific steps are the same as step 4 in Example 1).

[0190] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 100V, the time is 15min, and the duty cycle is 10%.

[0191] 5) The sample after anodizing surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as the silane coupling treatment in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polyether ether ketone with a molecular weight of 400,000 Daltons. The extraction time was 6s and the extraction speed was 2cm / s.

[0192] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0193] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 84 MPa, Young's modulus (E): 65 GPa, corrosion rate: 1.24 mm / y.

[0194] After polymer / anodic oxidation surface treatment: room temperature compressive strength (UCS): 103 MPa, Young's modulus (E): 62 GPa, corrosion rate: 0.66 mm / y.

[0195] Example 13

[0196] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0197] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional plasma rotating electrode method, with a particle size of 240 mesh.

[0198] 2) The magnesium alloy powder screened in step 1) is mixed with 260nm 45S5 bioglass powder, and the mass percentage of 45S5 bioglass powder in the mixed powder is 30%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0199] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 700W, the scanning speed to 500mm / s, the layer thickness to 0.04mm, and the interlayer rotation angle to 30°. Before printing, the substrate is heated to 25°C, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0200] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0201] The electrolyte used was the same as that used in step 4) of Example 1 for electropolishing and electrolyte composition. The oxidation voltage was 200V, the time was 8min, and the duty cycle was 10%.

[0202] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling treatment was performed (the specific steps are the same as those in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was polylactic acid-glycolic acid copolymer with a molecular weight of 400,000 Daltons. The extraction time was 4s and the extraction speed was 3cm / s.

[0203] The final performance test results of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps are as follows:

[0204] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 75 MPa, Young's modulus (E): 72 GPa, corrosion rate: 0.98 mm / y.

[0205] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 124 MPa, Young's modulus (E): 63 GPa, corrosion rate: 0.69 mm / y.

[0206] Example 14

[0207] This embodiment provides a controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold and its preparation method. The specific steps of the preparation method are as follows:

[0208] 1) Mg-4wt.%Y-3wt.%Gd-0.4wt.%Zr magnesium alloy powder was prepared by conventional gas atomization method, with a particle size of 300 mesh.

[0209] 2) Mix the magnesium alloy powder screened in step 1) with 300nm hydroxyapatite powder, and the mass percentage of hydroxyapatite powder in the mixed powder is 5%. The mixing process is carried out by ball milling (the specific steps are the same as step 2 in Example 1).

[0210] 3) The magnesium-ceramic glass powder obtained after mixing in step 2) is used for printing using LPBF. The laser power is set to 700W, the scanning speed to 600mm / s, the layer thickness to 0.04mm, and the interlayer rotation angle to 60°. Before printing, the substrate is heated to 50°C, and an inert gas (argon) is introduced during the printing process to ensure that the oxygen content in the working chamber is below 200ppm.

[0211] 4) Perform micro-arc oxidation surface treatment on the obtained printed parts. Before oxidation, perform electrolytic polishing and acid-base treatment (the specific steps are the same as step 4 in Example 1).

[0212] The electrolyte used has the same composition as the electrolyte in step 4) of Example 1, the oxidation voltage is 300V, the time is 5min, and the duty cycle is 10%.

[0213] 5) The sample after micro-arc oxidation surface treatment was subjected to polymer extraction treatment. Before the polymer extraction treatment, silane coupling KH550 treatment was performed (the specific steps are the same as the silane coupling treatment in step 5 of Example 1). The extraction solution used was a solution with a polymer material mass concentration of 10%. The polymer material selected was sodium alginate with a molecular weight of 600,000 Daltons. The extraction time was 4s and the extraction speed was 3cm / s.

[0214] The morphology of the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared through the above steps is shown in the figure below. Figure 2 As shown ( Figure 2 A represents the SEM morphology. Figure 2 B represents the macroscopic morphology of the stereomicroscope. The final performance test results are as follows:

[0215] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 83 MPa, Young's modulus (E): 62 GPa, corrosion rate: 0.87 mm / y.

[0216] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 111 MPa, Young's modulus (E): 59 GPa, corrosion rate: 0.56 mm / y.

[0217] Comparative Example 1

[0218] Comparative Example 1 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as that in Example 12, except that step 5 is omitted in this comparative example, that is, the sample after anodizing surface treatment is not subjected to polymer extraction treatment.

[0219] Tissue studies of the prepared magnesium-ceramic-glass composite scaffolds revealed that omitting the polymer extraction process prevented pore sealing of the coating, resulting in a large number of microporous structures on the scaffold surface. Corrosion solutions could then contact the magnesium alloy scaffold matrix through these microporous structures, leading to microgalvanic corrosion reactions with the magnesium alloy. This resulted in deterioration of the corrosion resistance and mechanical properties of the magnesium alloy scaffold, which in turn increased the cytotoxicity of osteoblasts cultured on the magnesium alloy scaffold.

[0220] The results of the controlled-degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared by the above steps, the performance of the printed magnesium alloy scaffold, and the final room temperature compression and degradation performance of the MAO-surface-treated magnesium alloy scaffold are as follows:

[0221] Printed magnesium-ceramic-glass composite scaffold material: room temperature compressive strength (UCS): 84 MPa, Young's modulus (E): 65 GPa, corrosion rate: 1.24 mm / y

[0222] After anodizing surface treatment: room temperature compressive strength (UCS): 89 MPa, Young's modulus (E): 66 GPa, corrosion rate: 0.99 mm / y.

[0223] Comparative Example 2

[0224] Comparative Example 2 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 6, except that: in step 4), when printing using laser powder bed fusion technology (LPBF), the laser power used is 400W.

[0225] Observation of the prepared magnesium-ceramic-glass composite scaffold revealed numerous unfused defects. This was due to insufficient laser power, which failed to penetrate the powder bed, resulting in weak interlayer bonding. The composite coating sealing treatment could not completely cover and fill these unfused defects. The corrosive liquid contacted the magnesium alloy scaffold matrix through these defects, undergoing a micro-galvanic corrosion reaction with the magnesium alloy. This led to a deterioration in the corrosion resistance and mechanical properties of the magnesium-ceramic-glass composite scaffold, consequently increasing the cytotoxicity of osteoblasts cultured on the scaffold.

[0226] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0227] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 68 MPa, Young's modulus (E): 70 GPa, corrosion rate: 1.52 mm / y.

[0228] After polymer / anodic oxidation surface treatment: room temperature compressive strength (UCS): 98 MPa, Young's modulus (E): 60 GPa, corrosion rate: 0.71 mm / y.

[0229] Comparative Example 3

[0230] Comparative Example 3 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 5, except that the magnesium alloy powder used in step 1) is screened with a particle size of 400 mesh (the maximum value exceeding the parameter range is 300 mesh).

[0231] Microstructural observation of the prepared magnesium-ceramic-glass composite scaffold revealed that excessively fine alloy powder particle size resulted in poor powder flowability, uneven powder distribution during LPBF (Liquid Per Filtration), and the formation of porosity and incomplete fusion defects. This is because excessively fine powder particles tend to accumulate during the powder spreading process, making it difficult to form a uniform powder layer and affecting print quality. The composite coating sealing treatment could not completely cover and fill the incomplete fusion defects. The etchant could then contact the magnesium-ceramic-glass composite scaffold matrix through these defects, undergoing a micro-galvanic corrosion reaction with the magnesium alloy. This led to a deterioration in the corrosion resistance and mechanical properties of the magnesium-ceramic-glass composite scaffold, resulting in increased cytotoxicity of osteoblasts cultured on the scaffold.

[0232] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0233] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 53 MPa, Young's modulus (E): 65 GPa, corrosion rate: 1.44 mm / y.

[0234] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 85 MPa, Young's modulus (E): 59 GPa, corrosion rate: 0.71 mm / y.

[0235] Comparative Example 4

[0236] Comparative Example 4 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 8, except that: in step 4), when printing using laser powder bed fusion technology (LPBF), the laser power used is 1000w.

[0237] Microstructural observation of the prepared magnesium-ceramic-glass composite scaffold revealed that excessive laser power led to overmelting of the material, resulting in numerous pores and cracks, and reduced structural density. Overheated areas caused by excessive power were visible in the microstructure. This is because excessive laser power causes localized overheating of the material, leading to overmelting and pore formation, affecting the material's density and mechanical properties. The composite coating sealing treatment could not completely cover and fill the pores and cracks. The corrosive liquid contacted the magnesium-ceramic-glass composite scaffold matrix through the defect sites, undergoing a micro-galvanic corrosion reaction with the magnesium alloy. This deteriorated the corrosion resistance of the magnesium-ceramic-glass composite scaffold, thereby increasing the cytotoxicity of osteoblasts cultured on the magnesium alloy scaffold.

[0238] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0239] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 72 MPa, Young's modulus (E): 69 GPa, corrosion rate: 1.47 mm / y.

[0240] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 85 MPa, Young's modulus (E): 62 GPa, corrosion rate: 0.92 mm / y.

[0241] Comparative Example 5

[0242] Comparative Example 5 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 7, except that: in step 4), when performing surface treatment using micro-arc oxidation (MAO) technology, the oxidation working voltage used is 450V (the maximum value exceeding the parameter range is 400V).

[0243] Microstructure observation of the prepared magnesium alloy scaffold with micro-arc oxidation surface treatment revealed that excessive working voltage during micro-arc oxidation caused ablation of the film layer during the surface treatment process, resulting in a large number of black ablation pits and cracks on the film surface. At the same time, a large number of unclosed volcanic pile-like pores with large pore diameters were also present, which seriously affected the quality of film formation and the mechanical properties and corrosion resistance of the material.

[0244] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0245] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 84 MPa, Young's modulus (E): 64 GPa, corrosion rate: 0.82 mm / y.

[0246] Comparative Example 6

[0247] Comparative Example 6 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 12, except that: in step 4), when performing surface treatment using anodizing technology, the oxidation working voltage used is 60V (less than the minimum value of 100V in the parameter range).

[0248] Microstructural observation of the prepared anodized magnesium-ceramic glass composite scaffold revealed that an insufficient working voltage during anodizing resulted in an insignificant arc initiation during the surface treatment process, leading to smaller pores in the generated film. Consequently, the polymer could not effectively bond with the internal pores during the subsequent polymer sealing process, resulting in poor adhesion between the polymer and the oxide coating. This affected the mechanical properties and corrosion resistance of the material, ultimately causing the scaffold to exhibit cytotoxicity.

[0249] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0250] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 69 MPa, Young's modulus (E): 68 GPa, corrosion rate: 1.46 mm / y.

[0251] After polymer / anodic oxidation surface treatment: room temperature compressive strength (UCS): 94 MPa, Young's modulus (E): 59 GPa, corrosion rate: 0.82 mm / y.

[0252] Comparative Example 7

[0253] Comparative Example 7 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 6, except that the ZrO2 powder used in step 2) has a particle size of 500 nm (exceeding the parameter range of 200-300 nm).

[0254] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0255] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 66 MPa, Young's modulus (E): 56 GPa, corrosion rate: 1.32 mm / y.

[0256] After polymer / anodic oxidation surface treatment: room temperature compressive strength (UCS): 101 MPa, Young's modulus (E): 57 GPa, corrosion rate: 0.75 mm / y

[0257] Comparative Example 8

[0258] Comparative Example 8 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 7, except that the molecular weight of polylactic acid used in step 5) is 1 million Daltons (which is 400,000-600,000 Daltons higher than the parameter range).

[0259] Macroscopic tissue observation after immersion experiments in simulated human body fluids revealed that the high molecular weight of polylactic acid caused significant swelling of the polymer material during immersion. Obvious swelling bubbles were generated at the interface between the polymer and the micro-arc oxidation coating. The bubbles ruptured during subsequent immersion, and micro-galvanic corrosion occurred between the corrosive liquid and the magnesium-ceramic glass composite scaffold at this point, affecting the corrosion resistance of the material and leading to cytotoxicity of the scaffold.

[0260] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0261] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 68 MPa, Young's modulus (E): 63 GPa, corrosion rate: 1.06 mm / y.

[0262] After polymer / MAO surface treatment: room temperature compressive strength (UCS): 92 MPa, Young's modulus (E): 56 GPa, corrosion rate: 0.81 mm / y.

[0263] Comparative Example 9

[0264] Comparative Example 9 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 12, except that the molecular weight of the polylactic acid-glycolic acid copolymer used in step 5) is 300,000 Daltons (lower than the parameter range of 400,000-600,000 Daltons).

[0265] Macroscopic tissue observation after immersion experiments in simulated human body fluids revealed that the low molecular weight of polylactic acid-glycolic acid copolymer led to rapid degradation of the polymer material during immersion. This resulted in the failure of the sealing effect on MAO pores during long-term degradation, causing microgalvanic corrosion between the corrosive liquid and the magnesium-ceramic glass composite scaffold matrix at this location. This affected the mechanical properties and corrosion resistance of the material, and consequently led to cytotoxicity of the scaffold.

[0266] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0267] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 84 MPa, Young's modulus (E): 65 GPa, corrosion rate: 1.24 mm / y.

[0268] After polymer / micro-arc oxidation surface treatment: room temperature compressive strength (UCS): 90 MPa, Young's modulus (E): 60 GPa, corrosion rate: 0.78 mm / y.

[0269] Comparative Example 10

[0270] Comparative Example 10 provides a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold and its preparation method. The preparation method is basically the same as the specific steps of Example 4, except that the micro-arc oxidation working time used in step 4) is 3 min (lower than the parameter range of 5-15 minutes).

[0271] Tissue observation of the prepared micro-arc oxidation surface-treated magnesium alloy scaffold revealed that the micro-arc oxidation working time was too short, resulting in a thin micro-arc oxidation coating, which led to poor corrosion resistance and mechanical properties of the magnesium alloy scaffold. Consequently, osteoblasts cultured on the orthopedic magnesium-ceramic glass composite scaffold experienced increased cytotoxicity.

[0272] The results of the final room temperature compression and degradation performance tests of the controllable degradable medical orthopedic magnesium-ceramic-glass composite scaffold prepared through the above steps are as follows:

[0273] Printed magnesium-ceramic glass composite scaffold material: room temperature compressive strength (UCS): 64 MPa, Young's modulus (E): 80 GPa, corrosion rate: 1.08 mm / y.

[0274] After polymer / MAO oxidation surface treatment: room temperature compressive strength (UCS): 112 MPa, Young's modulus (E): 67 GPa, corrosion rate: 0.76 mm / y.

[0275] The above description of the embodiments is provided to enable those skilled in the art to understand and use the present invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold, characterized in that, The method includes the following steps: A. Prepare magnesium alloy powder according to the preset composition; B. Mix magnesium alloy powder with ceramic glass powder; C. Composite material scaffolds were printed using laser powder bed melting technology; D. Perform an oxidation surface treatment on the composite material scaffold; E. Perform polymer coating surface treatment on the oxidized surface-treated support; In step A, the magnesium alloy is a Mg-Y-Gd-Zr series magnesium alloy. In step B, the ceramic glass includes at least one of hydroxyapatite, β-tricalcium phosphate, bioglass, and ZrO2; In step C, the parameters for printing using laser powder bed fusion technology include: laser power of 600-800w; layer thickness of 0.02-0.04mm; scanning speed of 400-600mm / s; and interlayer rotation angle of 0-90°.

2. The method for preparing the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold according to claim 1, characterized in that, In step A, the magnesium alloy powder is prepared by at least one of the following methods: gas atomization, centrifugal atomization, mechanical pulverization, or plasma rotating electrode method. The magnesium alloy powder has a particle size of 200-300 mesh.

3. The method for preparing the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold according to claim 1, characterized in that, In step B, the particle size of the ceramic glass powder is 200-300 nm; The bioglass includes at least one of 13-93 bioglass, 45S5 bioglass, and S53P4 bioglass. The ceramic glass powder has a mass content of 5-30% in the magnesium-ceramic composite powder.

4. The method for preparing the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold according to claim 1, characterized in that, In step C, before the laser powder bed melting technology is used for printing, the substrate needs to be heated to 25-400°C; during the printing process, inert gas needs to be introduced to keep the oxygen content in the working chamber below 200ppm.

5. The method for preparing the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold according to claim 1, characterized in that, In step D, the oxidation surface treatment is selected from at least one of micro-arc oxidation surface treatment and anodic oxidation surface treatment; The conditions for the micro-arc oxidation surface treatment are as follows: the working voltage is 200-400V, the oxidation time is 5-15min, and the duty cycle is 8-12%. The conditions for the anodic oxidation surface treatment are as follows: the working voltage is 100-200V, the oxidation time is 5-15min, and the duty cycle is 8-12%.

6. The method for preparing the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold according to claim 5, characterized in that, The electrolyte used in the oxidation surface treatment is mainly a silicate system with a concentration of 12-18 g / L.

7. The method for preparing the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold according to claim 1, characterized in that, In step D, before the composite material support undergoes oxidation surface treatment, the composite material support is further subjected to electrolytic polishing and acid-base treatment. The electrolyte used in the electropolishing is a mixed solution of nitric acid and alcohol, the voltage is 20-30V, and the polishing time is 2-4 minutes. The specific steps of the acid-base treatment are as follows: place the sample in a 6-10 g / L NaHCO3 solution for 8-12 seconds for alkaline washing, then rinse with water, and then wash with an 8-12 g / L phosphoric acid solution for 12-18 seconds, followed by rinsing with water.

8. The method for preparing the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold according to claim 1, characterized in that, In step E, the specific operation of performing the polymer coating surface treatment is as follows: the composite material scaffold is immersed in an extraction solution containing polymer materials for immersion treatment; the immersion time is 3-6 seconds and the immersion speed is 1-3 cm / s. The polymeric material is at least one of polylactic acid, polylactic acid-glycolic acid copolymer, polyetheretherketone, and sodium alginate; the molecular weight of the polymeric material is 400,000-600,000 Daltons. The mass concentration of polymeric materials in the extract is 8-12%.

9. The method for preparing the controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold according to claim 1 or 8, characterized in that, In step E, before performing the polymer coating surface treatment, the composite material scaffold is further subjected to a silane treatment step. The specific operation of the silane treatment is as follows: immerse the composite material scaffold in the silane coupling agent solution for 2-4 minutes, then lift it twice at a lifting speed of 0.7-1.2 cm / s, and then dry it.

10. A controllable degradable medical orthopedic magnesium-ceramic glass composite scaffold prepared according to any one of claims 1-9.